2014
DOI: 10.1186/1471-2474-15-350
|View full text |Cite
|
Sign up to set email alerts
|

Influence of osteogenic stimulation and VEGF treatment on in vivo bone formation in hMSC-seeded cancellous bone scaffolds

Abstract: BackgroundTissue engineering approaches for reconstruction of large bone defects are still technically immature, especially in regard to sufficient blood supply. Therefore, the aim of the present study was to investigate the influence of osteogenic stimulation and treatment with VEGF on new bone formation and neovascularization in hMSC-loaded cancellous bone scaffolds in vivo.MethodsCubic scaffolds were seeded with hMSC and either cultured in stem cell medium or osteogenic stimulation medium. One osteogenicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The in vivo results showed that cell‐seeded bone grafts precultured in osteogenic medium generated higher functional microvascular networks than those precultured in based medium. Interestingly, another study showed the similar neovascularization of BM‐MSC‐seeded bone grafts with or without VEGF treatment . These results further implicated that BM‐MSCs have the ability to secrete VEGF .…”
Section: Multipotent Stem Cellsmentioning
confidence: 71%
See 1 more Smart Citation
“…The in vivo results showed that cell‐seeded bone grafts precultured in osteogenic medium generated higher functional microvascular networks than those precultured in based medium. Interestingly, another study showed the similar neovascularization of BM‐MSC‐seeded bone grafts with or without VEGF treatment . These results further implicated that BM‐MSCs have the ability to secrete VEGF .…”
Section: Multipotent Stem Cellsmentioning
confidence: 71%
“…Interestingly, another study showed the similar neovascularization of BM-MSC-seeded bone grafts with or without VEGF treatment. 101 These results further implicated that BM-MSCs have the ability to secrete VEGF. 54,55 Compared with mono-culture system, co-culture of BM-MSCs and ECs (seen in Table II) or EPCs (seen in Table V) have showed the significant improvement of tissue neovascularization in most studies.…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 80%
“…[4][5][6][7][8] Moreover, some methods to seed stem cells into the gra materials have been reported, but in these techniques, the cell viability in the deep portion of large scaffolds is compromised as a result of poor vascularization and following hypoxia and inadequate nutrient transport. [9][10][11] In general, problems in functional vascularization lead to a lack of gra integration and the ultimate failure of craniomaxillofacial tissue-engineered products.…”
Section: Introductionmentioning
confidence: 99%
“…Bone healing can be improved by adjusting the speed of vascularization and during the last 5 years, attempts have been made to increase vascularization in the tissue-engineering field [27-29, 33, 38-39]. Hence, basic strategies using scaffolds focused firstly on the use of cells (HUVEC, EPC) [30][31][32], and secondly on the use of active molecules (VEGF, Ang1, ...) operating on endothelial cells [34][35][36] to promote proliferation, migration, sprouting and establishment of functional blood vessel. In our strategy, we chose to use not only VEGF active molecules (VEGF-NPs), but also endothelial and mesenchymal cells.…”
Section: Double Effect Of Vegf-nps Active 3d Pcl and Hob On Endothelimentioning
confidence: 99%
“…The prosthesis domain aims for replacement after ablation due to severe injuries, the bone substitute domain, targets the substitution of important lesions (until 60 cm [27][28][29]33]. In order to increase vascularization within the implanted site, several active angiogenic materials were developed with majority based on cell activities [34][35][36] or added factors activity [30][31][32]. One of the main growth factor involved in angiogenesis is VEGF165 (Vascular Endothelial Growth Factor) which acts as an initiator and a modulator of the signaling cascade resulting in proliferation and migration of endothelial cells toward formation of new blood vessels [37,38].…”
Section: Introductionmentioning
confidence: 99%